Glycated hemoglobin A1c as a risk factor for severe hypoglycemia in pediatric type 1 diabetes. Issue 1 (29th December 2015) - Karges, Beate; Kapellen, Thomas; Wagner, Verena M; Steigleder‐Schweiger, Claudia; Karges, Wolfram; Holl, Reinhard W; Rosenbauer, Joachim; ,
Abstract : Objective: To assess the risk of severe hypoglycemia related to glycated hemoglobin A1c (HbA1c) levels in a population‐based cohort of pediatric type 1 diabetes patients during two time periods since 1995. Methods: The association between HbA1c levels and severe hypoglycemia (defined as requiring assistance from another person) or hypoglycemic coma (loss of consciousness or seizures) was analyzed by multivariable regression analysis in children and adolescents with type 1 diabetes from the DPV Diabetes Prospective Follow‐up in Germany and Austria in 1995–2003 (n = 15 221 patients) and 2004–2012 (n = 22 318 patients). Results: Mean adjusted rates of severe hypoglycemia and hypoglycemic coma decreased from 19.18 [95% confidence interval (CI), 17.95–20.48] and 4.36 (3.93–4.83) per 100 patient‐years in 1995–2003 to 15.01 (14.18–15.88) and 2.15 (1.94–2.39) in 2004–2012, respectively (p < 0.001). From the first to the second period, the relative risk (RR) for severe hypoglycemia and hypoglycemic coma per 1% lower HbA1c decreased from 1.22 (1.15–1.30) to 1.06 (1.01–1.12) and from 1.27 (1.15–1.40) to 1.04 (0.94–1.16), respectively. Risk of severe hypoglycemia and coma declined most in patients with HbA1c levels of 6–6.9% (RR 0.70 and 0.43, respectively) and with HbA1c of 7–7.9% (RR 0.63 and 0.38, respectively). Mean HbA1c levels fell from 8.4% in 1995–2003 to 8.2% in 2004–2012, while the use of insulin pumps, short‐ and long‐acting insulin analogs, and glucose monitoring increased (p < 0.001). Conclusions: In contrast to 1995–2003, low HbA1c has become a minor risk factor for severe hypoglycemia and coma in pediatric patients with type 1 diabetes in the 2004–2012 period.